Observation of treatment of uremic skin pruritus with different-frequency hemoperfusion combined with hemodialysis and nursing during treatment - TAN Su-fen; CHENG Jian-ping; CHEN Yu-ping; LI Zhi-ting (Linchuang shenzangbing zazhi)
Objective To investigate the clinical efficacy and nursing of different-frequency hemoperfusion combined with hemodialysis(HP+HD) for treatment of uremic skin pruritus. Methods A total 80 patients with uremic skin pruritus were enrolled and divided into 4 groups, with 20 cases for each group. The control group(group A) was treated with routine hemodialysis(HD) 3 times per week; the other 3 trial groups(group B, C and D) were treated with the combination of hemoperfusion at different frequencies with hemodialysis(HP+HD), once per week for group B, twice per week for group C, and once per two weeks for group D. Skin pruritus severity for each group before and after treatment was scored, and concentrations of phosphorus, calcium and parathyroid hormone(PTH), and calcium-phosphorus product were determined and compared between them. Results The severity of skin pruritus in the trial groups was improved after treatment(P<0.05); the improvement outcome in group B, C was more significant than that in group D(P<0.05), but there was no significant difference between group B and group C(P>0.05). Serum PTH decreased after the treatments in all of the trial groups(P<0.05), but the decrease was greater in groups B and C than in group D(P<0.05). There was no significant difference between group B and group C(P>0.05). The serum phosphorus and calcium-phosphorus product in each trial group showed an overall decreasing trend(P<0.05), but there was no significant difference in serum calcium concentration before and after treatment(P>0.05). Conclusions The use of weekly hemoperfusion can not only improve uremic skin pruritus of uremia and achieve the clinical efficacy for PTH clearance, but also significantly reduce the cost of treatment, which is worthy of promotion in clinical practice.